(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The need to improve computer application competencies of graduates of Office Technology and Management (OTM) programme based on persistent complaints on their lack of the relevant competencies by employers necessitated this study on administrative supervisors’ assessment of database management and webpage design competencies possessed by OTM graduate workers in North-West Nigeria polytechnics.Two research questions guided the study and four null hypotheses were tested.Descriptive survey research design was used for the study.The population was 378 administrative supervisors in state and federal polytechnics. The population was used as sample. A structured 5-point rating scale questionnaire containing 36 items in two clusters was validated by three experts from the Faculty of Education, Nnamdi Azikiwe University, Awka and used for data collection. The reliability of the instrument was established using split-half with Pearson Product Moment Correlation Co-efficient formula and reliability co-efficient value of 0.78 was obtained. Mean and standard deviation were employed to answer the research questions and determine the homogeneity of the respondents’ views while t-test was used to test the null hypotheses at 0.05 level of significance. Findings revealed that the OTM graduate workers possessed database management competencies at a moderate level and possessed webpage design competencies at a little level. Gender and ownership of the institution influenced the respondents’ views on database management competencies of the OTM graduate workers but did not on webpage design competencies. Based on the findings, it was concluded that the OTM graduate workers in polytechnics in North-West Nigeria do not possess the relevant competencies for effective utilization of database management and webpage design applications. It was, therefore, recommended among others that OTM graduate workers in North-West Nigeria Polytechnics should seek out and utilize selfsponsored opportunities to improve their level of competencies in the two applications to enable them perform their duties effectively.